Mathematical Modeling in Statistical Activities: Key Episodes for Model Generation - Aymerich, Àngels; Albarracín, Lluís (Uniciencia, 2022)
This work is intended to assist 15-year-old secondary school students to learn about statistics using mathematical modeling. Specifically, open statistical problems are presented in which real social phenomena are studied by students using large data sets that comply with the design principles of model-eliciting activities. The tasks assigned are aimed at presenting the concept of variability and its application to understanding the situations studied using a mathematical model. The study focuses on identifying key episodes in the activities in which progress is made in the construction of mathematical models, and the elements that promote them. To do so, a qualitative analysis is carried out based on records of the students’ group work in the classroom using Modeling Activity Diagrams. The results obtained show that decisions about the design of a problem, such as using large amounts of data, or the ambiguity of social concepts such as “fair taxation,” are essential for promoting the development of mathematical models. The conclusions of this investigation have implications for the design of statistical tasks, and also for identifying the role of mathematical modeling in the learning of statistical concepts.